Local Modalities for Preventing Surgical Site Infections: An Evidence-based Review. Issue 1 (1st January 2018) - Katarincic, Julia A.; Fantry, Amanda; DePasse, J. Mason; Feller, Ross
Abstract : Surgical site infections remain a dreaded complication of orthopaedic surgery, affecting both patient economics and quality of life. It is important to note that infections are multifactorial, involving both surgical and patient factors. To decrease the occurrence of infections, surgeons frequently use local modalities, such as methicillin-resistant Staphylococcus aureus screening; preoperative bathing; intraoperative povidone-iodine lavage; and application of vancomycin powder, silver-impregnated dressings, and incisional negative-pressure wound therapy. These modalities can be applied individually or in concert to reduce the incidence of surgical site infections. Despite their frequent use, however, these interventions have limited support in the literature.